EFFECT OF PHOTON ENERGY ON THE RADIATION SENSITIVITY OF HEMA POLYMER GEL DOSIMETER BASED ON NEAR INFRARED EVALUATION (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigates the photon energy dependence of HEMA polymer gel dosimeters (PGDs) with maltose additive, evaluated using near-infrared (IR) spectrophotometry. Two batches of PGDs with varying maltose concentrations (0–520 mM) were irradiated using 6 MV and 10 MV photon beams. Absorbance-dose response curves were plotted, and sensitivities were compared using regression analysis and ANOVA. Results indicated a significant difference in sensitivity between the two photon energies (p < 0.05), suggesting photon energy dependence in the evaluated HEMA PGDs. These findings emphasize the need for energy-specific calibration when using HEMA PGDs in clinical applications.
Keywords: HEMA Polymer Gel Dosimeter; Energy Independence; Sensitivity of Polymer Gel Dosimeter; Maltose Additive